Eficiência de escórias de siderurgia na cultura do feijoeiro em sistema de semeadura direta - Deus, Angélica Cristina Fernandes [UNESP]; Büll, Leonardo Theodoro [UNESP] (FapUNIFESP (SciELO), 2013)
In the no till system, soil acidity correction practice is restricted to limestone use and there is little information regarding slag. The study aimed to evaluate the amendments in soil chemical properties, yield and bean nutrient uptake according to the application forms of slags, compared to limestone, in the implantation of no till system. The experiment was conducted in the field at College of Agricultural Sciences, Botucatu (SP) from December 2010 to May2011. The treatments consisted of two application ways of seven soil acidity correctives: steel slag, blast furnace slag, ladle furnace slag, stainless steel slag (agrosilício), wollastonite, lime and calcined dolomite lime, plus one control without corrective application. Each material dose was calculated to raise the base saturation to 70%. Soil acidity was neutralized down to 20cm with limestones, whereas for wollastonite and ladle furnace slag those effects occurred down to 10cm, for steel slag, blast furnace slag and agrosilício the corrective effect was restricted to the first 5cm. The bean yield increased by application of correctives in soil acidity, without differences between the application ways.
Efficiency of steel slag in the common bean crop in the no-till system
Keywords: Liming; Phaseolus vulgaris; Silicates